2022
DOI: 10.1088/2631-8695/ac90a0
|View full text |Cite
|
Sign up to set email alerts
|

Near dry turning of EN8 and EN31 steel: multi-objective optimization using grey relational analysis

Abstract: Steel is the most commonly employed material in various engineering applications, and their successful machining demands finding the optimized set of machining parameters along with appropriate cooling strategies. Moreover, the significance of process parameter optimization is progressively perceived in the wake of expensive CNC machine adaptation on the shop floor for machining. Further, a competent cooling strategy is essential with a minimal amount of coolant to obtain the best quality products. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…GRA is one of the most popular models of grey system theory. Fewer data with inadequate descriptions are present in grey systems, making it unable to use traditional statistical assumptions [17]. The contradicting nature of performance characteristics in multi-response problems leads to uncertainty.…”
Section: Grey Relational Generationmentioning
confidence: 99%
“…GRA is one of the most popular models of grey system theory. Fewer data with inadequate descriptions are present in grey systems, making it unable to use traditional statistical assumptions [17]. The contradicting nature of performance characteristics in multi-response problems leads to uncertainty.…”
Section: Grey Relational Generationmentioning
confidence: 99%
“…The result showed that the responses were highly influenced by F r followed by D c and C s . A study on the optimization of process parameters was performed by Mian and team for Near Dry Turning (NDT) of two steel grades, EN8 and EN31 [22]. Near Dry Turning was adopted with minimal amount of coolant with a predominant use of compressed air.…”
Section: Introductionmentioning
confidence: 99%
“…The primary shear zone, deformation zone, and worn-out flanks of the three main sources of heat generation during machining and mechanical alloying. This heat has an impact on surface characteristics [4]. The amount of contamination in the diamond and the presence of metallic elements help to determine the temperature of graphitisation [5].…”
Section: Introductionmentioning
confidence: 99%